(untitled) (Journal of Medical & Health Sciences Review, 2025)
Helicobacter pylori is a globally prevalent gastric pathogen implicated in chronic gastritis, peptic ulcer disease, and gastric cancer. Among its numerous virulence factors, the cagA and vacA genes play pivotal roles in determining disease severity. This study aimed to evaluate the molecular relationship between these virulence genes and the severity of gastric mucosal damage in H. pylori-infected patients. A total of 120 dyspeptic patients undergoing endoscopy were enrolled, of whom 82 were confirmed H. pylori-positive by histology, rapid urease test, and PCR. The presence of cagA and vacA genotypes (s, m, and i regions) was determined via PCR, and their associations with histopathological changes, endoscopic findings, and clinical outcomes were analyzed. The cagA gene was detected in 73.2% of infected patients, while the most virulent vacA genotype (s1/m1/i1) was present in 51.2%. Co-expression of cagA and vacA s1/m1/i1 was significantly associated with increased inflammation, glandular atrophy, intestinal metaplasia, and higher rates of duodenal and gastric ulcers (p < 0.001). Multivariate logistic regression identified vacA s1/m1/i1 (OR = 4.2, p = 0.001) and cagA (OR = 2.6, p = 0.03) as independent predictors of peptic ulceration. Additionally, high rates of antibiotic resistance were observed, particularly to metronidazole and clarithromycin. In conclusion, cagA and vacA genotyping provides valuable prognostic information regarding disease severity in H. pylori infection. These findings support the integration of molecular profiling into clinical risk assessment and personalized treatment strategies.